Evaluation of Analgesic Efficacy and Opioid-sparing Effect of Duloxetine After Arthroscopic Rotator Cuff Repair: A Randomized Clinical Trial. Issue 5 (22nd May 2022) - Su, Peng; Pang, Long; Li, Shu; Sun, Weihao; Zhao, Yanmin; Fu, Weili; Li, Jian; Tang, Xin
Abstract : Objective: This study aimed to evaluate the analgesic efficacy and opioid-sparing effect of duloxetine in adults having arthroscopic rotator cuff repair, as well as its clinical safety. Methods: In this randomized trial, 120 adults having arthroscopic rotator repair were randomized to receive perioperative oral duloxetine or placebo. The primary outcome was patient self-reported pain score (Visual Analog Scale: 0 to 10) at rest and opioid consumption within postoperative 2 days. Other outcomes included adverse effects, changes of thromboelastogram, and hemoglobin indicators before and after the operation. Results: A total of 120 patients were included in the intention-to-treat analysis, of which 60 received duloxetine and 60 received placebo. Groups were similar on the demographic, baseline, and intraoperative variables. There were significant differences in pain scores at rest at postoperative 3, 6, 12, 24, and 48 hours (3 h: P =0.001; 6 h: P =0.001; 12 h: P =0.001; 24 h: P =0.005; 48 h: P =0.034) and at movement at postoperative 6, 12, and 48 hours (6 h: P =0.004; 12 h: P =0.002; 48 h: P =0.033), while none of the differences met the minimum clinically important difference. There were no significant differences in opioid consumption and in hemoglobin and thromboelastogram before and after operation between the duloxetine group and the placebo group (all P >0.05). For adverse effects, the incidence of nausea and vomiting in the duloxetine group was significantly higher than that in the placebo group ( P =0.018). Discussion: For patients undergoing arthroscopic rotator cuff repairs, duloxetine resulted in a significant reduction in pain within postoperative 2 days, but the reduction was not clinically meaningful. Duloxetine did not decrease the opioid consumption within postoperative 2 days and did not increase the risk of bleeding within postoperative 2 days. The incidence of nausea and vomiting in the duloxetine group was significantly greater than that in the placebo group.